2020
DOI: 10.1186/s40862-020-00096-w
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method study of Iranian EFL teachers’ achieving resiliency: implications for teacher development

Abstract: The present study was an endeavor to investigate the differences between novice and experienced teachers' achieving resiliency in an explanatory sequential mixed method study. Forty Iranian (i.e., 20 novice and 20 experienced) teachers, male and female, participated in the present study in quantitative study who were selected through convenience sampling method from several private language institutes in Tabriz with teaching experience between 2 and 15 years. The Connor and Davidson Resilience Scale (CD-RISC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Likewise, Rizqi (2017) ran a case study in Indonesia on the role of stress in shaping teachers' resilience and found that teachers' positive emotions, supportive relationships, and calm working environment reduce stress and help changing it to resilience. Similarly, Entesari et al (2020) conducted a mixed-methods study on novice and experienced EFL teachers' resiliency and identified that experienced teachers are more resilient and employ more coping strategies when they face adversities. Moreover, in China, Qiong et al, 2019 conducted a correlational study on work conditions and relational trust and teachers' resilience and found that the quality of these variables can significantly predict teachers' resilience.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Likewise, Rizqi (2017) ran a case study in Indonesia on the role of stress in shaping teachers' resilience and found that teachers' positive emotions, supportive relationships, and calm working environment reduce stress and help changing it to resilience. Similarly, Entesari et al (2020) conducted a mixed-methods study on novice and experienced EFL teachers' resiliency and identified that experienced teachers are more resilient and employ more coping strategies when they face adversities. Moreover, in China, Qiong et al, 2019 conducted a correlational study on work conditions and relational trust and teachers' resilience and found that the quality of these variables can significantly predict teachers' resilience.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…This is a reasonable conclusion, as most instructors were compelled to teach online during the COVID-19 pandemic. Previous studies exploring resilience among educators have also found experience to be a significant factor in the development of resilience (Entesari et al, 2020;McDermid et al, 2016). One research study exploring resilience among nurse educators teaching online courses suggested that faculty who teach online may have higher levels of resilience because of the amount of time and patience required to teach using this modality (Wilson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Resilience and self-efficacy have a reciprocal relationship in individuals who teach others. Resilient teachers are self-confident, are optimist, and have higher levels of self-efficacy and strong supportive peer networks (Entesari et al, 2020). Higher levels of resilience help faculty assimilate various protective factors, such as resources, attributes, and skills, to mitigate stress and deal with challenges.…”
Section: Implications For Nurse Educatorsmentioning
confidence: 99%
“…Length of teaching experience may help build resilience, as demonstrated by Entesari et al (2020). Supportive collegial relationships, assessments that focus on positive outcomes, and reflections on how one overcomes challenges while adapting to their new role have also been shown to increase resilience.…”
mentioning
confidence: 99%